Pengaruh Moral Wajib Pajak Orang Pribadi terhadap Persepsi atas Tax Evasion dengan Kepatuhan Wajib Pajak sebagai Variabel Mediasi - Joe Elsa Indriyani; Riana Sitawati; Subchan Subchan (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2018)
The purpose of this study is to be able to analyze the effect of moral on perception of tax evasion mediated by taxpayer compliance. Calculation of the number of research samples using Slovin formula, the sample in the study was as many as 100 questionnaires distributed directly in Central Semarang Two Primary Tax Office with the permission of the official in charge of the Tax Office. Data analysis uses the WarpPLS 4.0 program with Partial Least Square (PLS) approach. The Results of previois studies as follows moral has a positive effect on the compliance. Compliance has a negative effect on perception of tax evasion. Moral has a negative effect on perception of tax evasion. Compliance mediates the effect of moral on perception of tax evasion.